2011
DOI: 10.1016/j.ultras.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Elastic surface waves in crystals. Part 1: Review of the physics

Abstract: We present a review of wave propagation at the surface of anisotropic media (crystal symmetries). The physics for media of cubic and hexagonal symmetries has been extensively studied based on analytical and semi-analytical methods. However, some controversies regarding surfaces waves and the use of different notations for the same modes require a review of the research done and a clarification of the terminology. In a companion paper we obtain the full-wave solution for the wave propagation at the surface of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…Besides the reflected bulk waves listed above, it is found that there emerges a reflected surface localized at the boundary and propagates parallel to the boundary. Other than the general surface wave , the reflected surface wave should satisfy the boundary conditions of Eq. together with other reflected bulk waves viz.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the reflected bulk waves listed above, it is found that there emerges a reflected surface localized at the boundary and propagates parallel to the boundary. Other than the general surface wave , the reflected surface wave should satisfy the boundary conditions of Eq. together with other reflected bulk waves viz.…”
Section: Resultsmentioning
confidence: 99%
“…The range is simply the one for which waves have a normal to the slowness surface (proportional to the group velocity) that points towards the abscissa axis. There exists a well-known close connection [38,40,60,73] between the problem of a uniformly-moving dislocation in an anisotropic media, and the theory of surface waves and of wave reflection at interfaces in anisotropic media (see, e.g., [39,74,75] for recent reviews). In the latter context, it is remarked that waves with such normals have been interpreted as incident waves onto the interface [73].…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Various ways to deal with such surface wave solutions are carefully reviewed by Every et al 22 and Favretto-Cristini et al 23 Facile measurement of elastic constants X Du and J-C Zhao…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, RW is "subsonic" and thus it can be identified along any given propagation orientation as the peak with a velocity lower (higher slowness) than that of the ST wave (only in extremely rare cases the RW velocity is "supersonic" and such situations can be identified by the full surface and bulk wave calculations). 22,23 For orientations along which the RW is too weak to be observable, the PSAW is selected as the SAW. This is accomplished by a first search of the RW peak in the slowness region above that of the ST wave; and in the absence of an observable RW peak, the program/algorithm selects the first peak with the slowness lower than that of the ST wave.…”
Section: Introductionmentioning
confidence: 99%